Peningkatan perawatan diri pasien skizofrenia dengan teknik positive reinforcement - Arbita Wafdatul Ilmia (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Schizophrenia is a chronic  mental disorder characterized by hallucinations, delusions, withdrawal from the  social environment and failure of life functions.  Self-care in schizophrenic patient  becomes a serious problem and if it is left untreated, it will worsen  the patient’s situation. This case study aimed to improve self-care of schizophrenic patient by utilizing the positive reinforcement. Psychological assessment used  was interviews, observations, grafis test, wartegg, SPM, and WWQ. The intervention  was given using a behaviour therapist with Skinner’s approach which consisted of 7 sessions. The subject was male,  aged 31 years old. The intervention revealed a positive result,  i.e., the subject became more  active to take care  of himself properly  starting  from brushing his teeth, watering all parts  of his body, and wearing  outfit properly.